VD_FINDINFO 36/2009/JKR vom 23. Januar 2009 - VD Tribunal cantonal (2009)
CÉDULE HYPOTHÉCAIRE, TITRE AU PORTEUR, COMPTE COURANT, RÉSILIATION IMMÉDIATE, CLAUSE INSOLITE, ABUS DE DROIT | 2 al. 1 CC, 2 al. 2 CC, 844 CC, 906 al. 1 CC, 164 al. 1 CO